2002
DOI: 10.1063/1.1522811
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of atomic layer deposited HfO2 gate dielectric layers on chemical oxide (Si–O–H) and thermal oxide (SiO2 or Si–O–N) underlayers

Abstract: A study was undertaken to determine the efficacy of various underlayers for the nucleation and growth of atomic layer deposited HfO2 films. These were compared to films grown on hydrogen terminated Si. The use of a chemical oxide underlayer results in almost no barrier to film nucleation, enables linear and predictable growth at constant film density, and the most two-dimensionally continuous HfO2 films. The ease of nucleation is due to the large concentration of OH groups in the hydrous, chemical oxide. HfO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
208
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(231 citation statements)
references
References 16 publications
12
208
3
2
Order By: Relevance
“…Such deposition is not straightforward and it has been found that the deposition behavior of a high-k layer can be highly dependent upon the starting surface. 5 Moreover, we have observed that metallorganic chemical vapor deposition ͑MOCVD͒ of HfO 2 on various starting surfaces results in the formation of an interfacial layer ͑IL͒ underneath the high-k layer, which obviously influences device performance. Furthermore, if this IL becomes too thick, the 1 and sub-1 nm equivalent oxide thicknesses ͑EOTs͒ targeted in the ITRS roadmap cannot be reached.…”
mentioning
confidence: 99%
“…Such deposition is not straightforward and it has been found that the deposition behavior of a high-k layer can be highly dependent upon the starting surface. 5 Moreover, we have observed that metallorganic chemical vapor deposition ͑MOCVD͒ of HfO 2 on various starting surfaces results in the formation of an interfacial layer ͑IL͒ underneath the high-k layer, which obviously influences device performance. Furthermore, if this IL becomes too thick, the 1 and sub-1 nm equivalent oxide thicknesses ͑EOTs͒ targeted in the ITRS roadmap cannot be reached.…”
mentioning
confidence: 99%
“…This component ratio of SC1 solution was developed by M. L. Green, etc., 23 and was modified in our previous work to be an effective method to grow interfacial layer for ALD of high quality HfO 2 . 26 Multi-angle spectroscopic ellipsometry (J.…”
Section: Methodsmentioning
confidence: 99%
“…OH termination of Si is crucial for the chemical attachment of metal precursors onto Si surface. 1,[18][19][20][21][22] It was found that the density of -OH groups on Si surface has an effect on the atomic surface roughness and dielectric leakage current of HfO 2 23 Ozone based wet chemical oxidation and ozonated water spraying are widely used in industry for ALD growth of HfO 2 . 24,25 The growth of the interfacial layer was controlled by ozone concentration in water.…”
mentioning
confidence: 99%
“…SC1 cleaning is commonly used in silicon IC processing and is known to produce an OH terminated SiO 2 surface [8,9]. (997) 2.2.…”
Section: Introductionmentioning
confidence: 99%